Stigmatising substance‐related language in the electronic health records of hospitalised patients after addiction consult service implementation - Ryder Cuppett; Justin Birge; Kristin Daniel; Alëna A. Balasanova (Internal Medicine Journal, 2026)
Abstract Objectives Stigmatising language about patients with substance use disorders (SUD) is common in healthcare settings and negatively impacts patient care. Addiction consult services are associated with improved clinician attitudes and less stigmatising views towards patients with SUD. We investigated whether implementation of an addiction consult service at a large urban medical centre was associated with changes in prevalence of stigmatising language in the electronic health record (EHR) of hospitalised patients and examined these changes across medical training levels. Methods We performed a retrospective analysis of all inpatient notes in the EHR 5 years before and after Addiction Consult Service implementation. Notes were queried using string term searches for stigmatising language related to SUD. Data were aggregated by author profile type and training level focusing on medical students, residents/fellows and attending physicians. We used chi‐squared tests to compare changes in the prevalence of stigmatising language. Results Overall percentage of notes containing stigmatising language decreased significantly from 7.70% before Addiction Consult Service implementation to 7.43% after ( P < 0.001). Among physicians in training, medical students had a 3.11% ( P < 0.001) decrease in notes containing stigmatising language and residents/fellows saw a 1.31% ( P < 0.001) decrease. In contrast, stigmatising language in attending physician notes increased by 0.84% ( P < 0.001). Conclusions Implementation of an Addiction Consult Service was temporally associated with decreased stigmatising language in documentation by medical students and residents/fellows, suggesting that exposure and education provided by an Addiction Consult Service may have positively influenced documentation practices. Increased stigmatising language in attending physician notes highlights the need for ongoing anti‐stigma education and training for practicing clinicians. These findings support the potential role of Addiction Consult Services in reshaping institutional culture around SUD.